PEMODELAN REGRESI BERGANDA UNTUK FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN PRODUK IMPLORA MENGGUNAKAN PLATFORM TIKTOK SHOP DI PURWAKARTA - Farida Apriani (Universitas Lambung Mangkurat, 2025)
The cosmetics industry in Indonesia is experiencing rapid growth and has managed to dominate the domestic market, so many cosmetic brands continue to innovate, including the Implora brand. Implora is a cosmetic that can be reached by all strategists looking to be known, namely promotions that use the tiktok shop application. Tiktok shop presents an innovative